The spreading of Alfalfa mosaic virus in lavandin in Croatia (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
A survey was conducted in 2012 and 2013 to detect the presence and distribution of Alfalfa mosaic virus (AMV) in lavandin crops growing in continental parts of Croatia. A total of 73 lavandin samples from six crops in different localities were collected and analyzed for the presence of AMV and Cucumber mosaic virus (CMV) using commercial double-antibody sandwich (DAS)-ELISA kits. AMV was detected serologically in 62 samples collected at three different localities, and none of the samples tested positive for CMV. For further analyses, six selected samples of naturally infected lavandin plants originating from different localities were mechanically transmitted to test plants: Chenopodium quinoa, C. amaranticolor, Nicotiana benthamiana and Ocimum basilicum, confirming the infectious nature of the disease. Molecular detection was performed by amplification of a 751 bp fragment in all tested samples, using the specific primers CP AMV1/CP AMV2 that amplify the part of the coat protein (CP) gene and 3’-UTR. The RT-PCR products derived from the isolates 371-13 and 373-13 were sequenced (KJ504107 and KJ504108, respectively) and compared with the AMV sequences available in GenBank. CP sequence analysis, conducted using the MEGA5 software, revealed that the isolate 371-13 had the highest nucleotide identity of 99.5% (100% amino acid identity) with an isolate from Argentina originating from Medicago sativa (KC881010), while the sequence of isolate 373-13 had the highest identity with an Italian AMV isolate from Lavandula stoechas (FN667967) of 98.6% (99% amino acid identity). Phylogenetic analysis revealed the clustering of selected isolates into four molecular groups and the lavandin AMV isolates from Croatia got into two distinct groups, implying a significant variability within the AMV lavandin population.
Keywords: Alfalfa mosaic virus; Lavandin; Molecular detection; Phylogenetic analysis; Croatia